Preparation of A Polymeric Mesh Supported with Nanomaterials to Treat Oil Slick Pollution in the River - S. Hamood, Sara; S. Khalaf, Majid; S. Mohammed, Firas (Al-Nahrain Journal of Science, 2024)
In this project, (ZnO, Ag, ZnO:PVP, Ag:PVP) nanoparticles were synthesized using a pulsed laser ablation method. Various techniques were employed for analyzing and characterizing the nano-products. More, the examination of X-ray technique for oxides indicated possessing Cubic: Cube-like, isometric formation, with a orie predominant orintation sideways (111), (100) and (200).  for silver nanoparticles, Zinc oxide and ZnO:Ag NPs respectively. Energy-dispersive X-ray spectroscopy transmission electron microscopy (TEM) analysis, X-ray fluorescence (XRF), Fourier-transform infrared spectroscopy, and photoluminescence measurements (PL) were among them. Membrane purification techniques are currently extensively utilized in environmental uses, such as water and wastewater treatment, as well as in various industries including agri-food and biotechnology. the study incorporated the use of polymer-supported nanomaterials, with PVP selected for its excellent chemical and thermal resistance. Various membrane structures with differing porosities were prepared and effectively employed for the filtration of oil-polluted water, as validated through TEM, XRF, and other measurements. In this context, the polymer functioned akin to a sponge for water pollution remediation.